2021
DOI: 10.31004/edukatif.v3i6.1659
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Modul Hypercontent Berorientasi HOTS

Abstract: Era pendidikan saat ini mengarahkan mahasiswa untuk memiliki higher Order Thinking Skill (HOTS), maka perlu adanya modul perkuliahan yang memfasilitasi mahasiswa untuk berpikir secara HOTS yang memudahkan mahasiswa mengakses berbagai sumber belajar. Penelitian ini bertujuan untuk menghasilkan produk yaitu  modul hypercontent berorientasi HOTS pada mata kuliah Genetika yang bersifat valid dan praktis. Penelitian ini berjenis research and development (R&D) dengan menggunakan model pengembangan yakni ADDIE (Analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Development research with the title of Higher Order Thinking Skills (HOTS) based module development is of course not the first, but of course, each research with such a title has its differences and advantages. Where both studies showed an increase in the percentage of learning outcomes, in the study service levels reached 91.3% and student cognitive learning outcomes increased from 67.4 before using the module and 85.3 after using the module (Anisa et al, 2021).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Development research with the title of Higher Order Thinking Skills (HOTS) based module development is of course not the first, but of course, each research with such a title has its differences and advantages. Where both studies showed an increase in the percentage of learning outcomes, in the study service levels reached 91.3% and student cognitive learning outcomes increased from 67.4 before using the module and 85.3 after using the module (Anisa et al, 2021).…”
Section: Discussionmentioning
confidence: 80%
“…They think that teaching materials provided school already enough, so no need again make or develop teaching materials, besides it's also the teacher is charged with administration must be done by the teacher, such as RPP making, design class, and so on, so Things this eat much time for teachers, and will the more confiscate time if they must make textbooks back, then they more choose to use existing textbooks (Hasanah, 2021;Utari & Gustiningsi, 2021). (Anisa et al, 2021) Whereas for practice students to have Skills analyze and think level tall no enough only with depending on textbooks provided school, the teacher must initiative help student with providing teaching materials that lead to the expected skills, with give appropriate teaching materials and exercises good question then Skills think level tall students will also be trained. Besides Things, the students will also be more practical bring teaching materials, or modules prepared by teachers, students will easily study where just and learn independently, as well as hope with the help given module student will provoked for find question new then discussed with teachers at school.…”
Section: Introductionmentioning
confidence: 99%